Analisis Pengaruh Parameter Proses Pada Kualitas Las SMAW Baja Paduan Stainless Steel 304 - Muhammad Siraj Mahfud; Bambang Dwi Haripriadi; Agnes Arum Budiana (Jurnal INOVATOR, 2025)
This study analyzes the effect of Shielded Metal Arc Welding (SMAW) welding process parameter variations on the quality of welded joints in 304 stainless steel by varying the current (65 A, 75 A, and 95 A), electrode diameter (2.0 mm; 2.6 mm; 3.2 mm), and weld type (I, V, and X). Evaluation is carried out through tensile tests to determine tensile load, stress, and strain, as well as Non-Destructive Test (NDT) dye penetrant method to detect surface defects. Taguchi L27 design is used to analyze the contribution of each parameter to the quality of the joint. The results show that current is the most influential factor on tensile strength, followed by electrode diameter and weld type. The optimal combination is obtained at a current of 95 A, a 3.2 mm electrode, and an X (double V) weld, with an average tensile load of 87.65 kN, a stress of 730.42 MPa, and a strain reaching 100% which shows the best mechanical performance. Overall, this study confirms that proper welding parameter settings are crucial for the mechanical integrity and quality of 304 stainless steel welded joints.